PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, STRUKTUR AKTIVA, LIKUIDITAS, DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL PERUSAHAAN (STUDI PADA PERUSAHAAN SUB SEKTOR TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Dewanti, Yossy Octa; wati, Andar (Jurnal Ilmiah Mahasiswa FEB, 2016)
The purpose of this study to determine the effect of profitability, firm size, asset structure, liquidity and business risks to capital structure. The independent variables are profitability, firm size, asset structure, liquidity and business risks. The dependent variable in this study is the capital structure. This study uses quantitative methods with explanatory type of research. The sampling technique used in this study are saturated sampling and obtained 15 samples. This study used secondary data obtained from the annual report from the Indonesia Stock Exchange (BEI) in the 2011-2014 period. The analytical methods used to analyze the data is multiple regression analysis were used to prove the hypothesis of the study. All data were analyzed using SPSS version 18. Result of the analysis on simultaneous test indicate that profitability, firm size, asset structure, liquidity and business risks together have a significant effect on the capital structure. Research on partial test shows that firm size have a positive relationship with the capital structure, as well as liquidity and business risks influential and have a negative relationship with the capital structure. Meanwhile, profitability and asset structure has no effect on the capital structure. Variable size of the company has a dominant influence on the capital structure. Â  Keywords: Capital Structure, Profitability, Firm Size, Company Size, Structure Asset, Liquidity, Risk Business.